PEDAL protocol: a prospective single-arm paired comparison of multiparametric MRI and 18F-DCPFyl PSMA PET/CT to diagnose prostate cancer. Issue 9 (19th September 2022) - Tran, Vy; Hong, Anne; Sutherland, Tom; Taubman, Kim; Lee, Su-Faye; Lenaghan, Daniel; Sethi, Kapil; Corcoran, Niall M; Lawrentschuk, Nathan; Woo, H; Tarlinton, Lisa; Bolton, Damien; et al.
Abstract : Introduction: Prostate-specific membrane antigen positron emission tomography (PSMA-PET) has emerged as valuable imaging to assessing metastatic disease in prostate malignancy. However, there has been limited studies exploring the utility PSMA-PET as primary imaging assessing for index lesions prior to biopsy. The primary objective of this study is to compare the diagnostic accuracy of 18-fluorine PSMA (18F DCFPyL PSMA) PET scans to multiparametric MRI (mpMRI) to detect primary prostate cancer at prostate biopsy. Methods and analysis: The PEDAL trial is a multicentre, prospective, single-arm, paired comparison, non-randomised phase III trial in subjects considered for diagnostic prostate biopsy. Subjects who are eligible for a diagnostic mpMRI prostate will undergo additional same-day 18 F DCFPyl PSMA PET/CT of the chest, abdomen and pelvis. Software coregistration of the mpMRI and PSMA-PET/CT images will be performed. The reporting of the mpMRI prostate, PSMA-PET/CT and PSMA PET/MRI coregistration will be performed blinded. The diagnostic accuracy of PSMA PET/CT alone, and in combination with mpMRI, to detect prostate cancer will be assessed. Histopathology at prostate biopsy will be used as the reference standard. Sample size calculations estimate that 240 subjects will need to be recruited to demonstrate 20% superiority of PSMA-PET/CT. The sensitivity, specificity, positive predictive value and negative predictive value of the combination of mpMRI prostate and PSMA PET/CT compared with targeted and systematic prostate biopsy will be evaluated. It is hypothesised that PSMA PET/CT combined with mpMRI prostate will have improved diagnostic accuracy compared with mpMRI prostate alone for detection of prostate cancer in biopsy-naïve men, resulting in a significant impact on patient management. Ethics and dissemination: This study was approved by the independent Human Research Ethics Committee. Results will be published in peer-reviewed medical journals with eligible investigators will significantly contribute. Trial registration number: ACTRN12620000261910.